2022
DOI: 10.3389/fnut.2022.985451
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of omega-3 polyunsaturated fatty acids on controlling blood pressure: An umbrella meta-analysis

Abstract: Several meta-analyses have revealed that n-3 PUFAs can lower blood pressure, but the findings are conflicting. In this regard, the present umbrella meta-analysis aimed was performed to clarify whether n-3 PUFAs have effects on blood pressure. PubMed, Scopus, Embase, Web of Science, and Google Scholar were used as international databases from inception to May 2022. To examine the effects of n-3 PUFA supplementation on blood pressure, a random-effects model was applied. The leave-one-out method was performed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Various meta‐analyses and RCTs have suggested that omega‐3 PUFAs supplementation might reduce serum levels of ALT, AST, GGT, and lipid content in NAFLD patients 8,11 . PPARs are activated by omega‐3 PUFAs, which impair the expression and activity of lipogenic enzymes andgenes, namely acetyl‐CoA carboxylase (ACC), fatty acid synthase (FAS), sterol regulatory element‐binding protein 1c (SREBP‐1c), carbohydrate responsive element‐binding protein (ChREBP), and HMG‐CoA reductase 21–25 . The activity and expression of PPAR may also increase lipoprotein lipase (LPL) activity, an enzyme involved in liver lipid metabolism and inflammation 26–28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various meta‐analyses and RCTs have suggested that omega‐3 PUFAs supplementation might reduce serum levels of ALT, AST, GGT, and lipid content in NAFLD patients 8,11 . PPARs are activated by omega‐3 PUFAs, which impair the expression and activity of lipogenic enzymes andgenes, namely acetyl‐CoA carboxylase (ACC), fatty acid synthase (FAS), sterol regulatory element‐binding protein 1c (SREBP‐1c), carbohydrate responsive element‐binding protein (ChREBP), and HMG‐CoA reductase 21–25 . The activity and expression of PPAR may also increase lipoprotein lipase (LPL) activity, an enzyme involved in liver lipid metabolism and inflammation 26–28 .…”
Section: Discussionmentioning
confidence: 99%
“…8,11 PPARs are activated by omega-3 PUFAs, which impair the expression and activity of lipogenic enzymes andgenes, namely acetyl-CoA carboxylase (ACC), fatty acid synthase (FAS), sterol regulatory element-binding protein 1c (SREBP-1c), carbohydrate responsive element-binding protein (ChREBP), and HMG-CoA reductase. [21][22][23][24][25] The activity and expression of PPAR may also increase lipoprotein lipase (LPL) activity, an enzyme involved in liver lipid metabolism and inflammation. [26][27][28] In addition, omega-3 PUFA consumption is thought to enhance the omega-3 PUFAs to omega-6 ratio in cells, which in turn results in a reduction in arachidonic acid-derived inflammatory eicosanoids and further inhibits liver fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed a strong link between omega-3 polyunsaturated fatty acids (n-3 PUFA) and anti-inflammatory impacts ( 3 5 ). Numerous systematic reviews and meta-analysis have noted that n-3 PUFAs exhibited anti-inflammatory effects on multiple non-communicable diseases, including systemic inflammatory response syndrome ( 3 ), colorectal cancer ( 4 ), type 2 diabetic mellitus ( 5 ), bipolar disorder ( 6 ), mental disorders ( 7 ), polycystic ovary syndrome ( 8 ), heart failure ( 9 ), hypertension ( 10 ), and rheumatoid arthritis ( 11 ). With respect to gout, experiments in vitro noted that n-3 PUFAs could inhibit the NLRP3 inflammasome in monocytes via downstream effects of a two-signal initiation system ( 12 , 13 ), including suppression of nuclear factor kappa-B (NF-κB) via Toll-like receptor 4 and Toll-like receptor 2 ( 14 ) and assembly of the inflammasome and activation of caspase-1 ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Omega-3 poly-unsaturated fatty acids (PUFAs) including eicosapentaenoic acid (EPA; 20:5) and docosahexaenoic acid (DHA; 22:6) ( Figure 1 A), which are the main components in oil derived from fish and other marine organisms, when used as a dietary supplement, have several benefits for human health. Although the omega-3 PUFAs real role in major cardiovascular risks is currently controversial, they may help to reduce the development of coronary heart diseases by decreasing hypertriglyceridemia [ 1 ], blood pressure [ 2 ], and the chronic immune-inflammatory response that underlies atherosclerosis [ 3 ]. Other interesting effects of EPA and DHA may derive from their antioxidant activities [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%